Pakolaistaustaisten oppilaiden tuki koulutoimen hallinnollisissa diskursseissa - Mustonen Sanna; Kaukko Mervi; Alisaari Jenni; Petäjäniemi Maria; Heikkola Leena Maria; Harju-Autti Raisa; Haswell Nick (Finland, 2025)
In this article, we examine Finnish school administration discourses concerning support for students with a refugee background. The data consisted of expert interviews and was analysed using a critical discourse analysis approach. Regarding learning support, we identified discourses concerning tensions between policy and practices, as well as the deus ex machina discourse. Regarding psychosocial support, the discourses of uncertainty, caution and deus ex machina were identified. Thus, built within the experts’ discourses there is a strong understanding of the importance of learning support but uncertainty regarding the need for psychosocial support. Two further discourses, those of exclusion and securitization discourses were also identified as significant in the reception of students with a refugee background. These two discourses were resisted by the experts we interviewed. The results indicate a continuing need for common policies at the national level to provide long-term support for refugee-background students as well as further teacher training development.
Kieli ja osallisuus. Språk och delaktighet. Language and participation